THE ROLE OF M. KROPYVNYTSKY’S THEATRE TROUPE IN PRESERVATION OF TRADITIONS OF THE UKRAINIAN NATION - Yan, Iryna (Collection of scientific papers «ΛΌГOΣ», 2022)
Ukrainian historical and cultural heritage is an important component of ethnic self-identification and presentation of our country in a multicultural European space. The activity of the first M. Kropyvnytsky’s Ukrainian theatre troupe is an important component of the national cultural and historical heritage, an inexhaustible source of preservation of ethnic traditions, worldview values, an artistic imperative of the spiritual sovereignty of Ukrainians.